Generator Assessment of Hydro Power Station Adequacy after Reconstruction from Classical to HIS SF6 Substation - Srete Nikolovski; Goran Slipac; Emir Alibašić (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Reliability analysis of substations and generator assessment of power plant stations are very important elements in a design and maintenance process. This paper presents a generator adequacy assessment of a classical “H” scheme for an open conventional substation, which is often used, and a new HIS - High Integrated Switchgear with SF6 gas isolation. Generator adequacy indices of both types of classical and HIS switchgear were compared and the results showed a high level of reliability and availability of the HIS presented substation. The input data were the annual reports of Croatian TSO-Transmission System Operator (HOPS) and statistics of operation events of Croatian National Electricity (HEP Inc.). For the HIS substation, the input reliability data were used from relevant international literature since only few of HIS substations are installed in Croatia. The generator is modelled with a three-state Markov state space model and Monte Carlo simulations were used for the generator assessment analysis. Adequacy indices LOLP and EDNS were obtained using DIgSILENT software.